Proposta de ensino de ondas sonoras com aplicação de experimentos simples em sala de aula - Silva, Mackson Kerlley Freire (2022)
We approach in this work a method of teaching waves through the construction and application of experiments for students in the classroom. The method was applied in classes of the 1st year of high school at Escola Mariano Martins, located in Henrique Jorge, Bairro de Fortaleza - Ce. From the use of low-cost materials, even recycled ones, a sequence of experiments was developed regarding the understanding of the study of sound waves. As a mentor of this sequence of experiences, I developed the dissertation in the form of an action research, presenting principles that guide the teaching of sound waves to the participants. The research involves the investigation of different elements linked to sound, as well as the classification of characteristics of different sounds produced by different means. Such work was only possible with an active search for experimental works in physics teaching, which every day presents such difficulty in learning in our society. In our theoretical framework, basically from Vygotsky, Valon, we respectively investigate issues related to science education from the use of simple experiments linked to subsumers, according to Ausubel, with the perspective of subsidizing a discussion around the pedagogical activities of teaching-learning physics. Regarding the theoretical review of physics, we perceive a great demand for good authors to theoretically explain any area of physics knowledge. Theory is still an essential part of teaching practice. Since it is through the theoretical basis that it was possible to develop the entire sequence of experiments contained in this work. In the field of physics teaching, we criticize some aspects of the so-called traditional teaching model, which does not seek to creatively explore the various phenomena around topics related to physics teaching. The results open doors to other proposals regarding teaching/learning in physics and to discussions about public policies for science education.